Pengaruh Kesadaran Wajib Pajak, Pengetahuan Pajak dan Pelayanan Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor pada PPSU Kelurahan Ceger - Qintari Setyaningrum; Erika Takidah; Santi Susanti (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of taxpayer awareness, tax knowledge, and tax services on motor vehicle taxpayer compliance among Public Facility Maintenance Officers (PPSU) in Ceger Sub-District. The research employs a quantitative approach with an associative method. The population consists of all 83 PPSU members in Ceger, and the sampling technique uses a census method. The research instrument was a Likert-scale questionnaire. Data analysis techniques include descriptive statistics, validity and reliability tests, classical assumption tests (normality, multicollinearity, heteroscedasticity), multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results indicate that partially, tax knowledge and tax services have a positive and significant effect on taxpayer compliance, while taxpayer awareness does not show a significant effect. Simultaneously, all three variables significantly influence motor vehicle taxpayer compliance. The practical implication of this study highlights the need to enhance tax education and improve service quality, particularly in accessibility and responsiveness of tax officers, to increase compliance levels, especially among government workers such as PPSU officers.